Filipino domestic workers rights and welfare discursive framings by NGOs in Hong Kong and the Philippines - Lopez-Wui, Ma. Glenda (Philippine Sociological Review, 2015)
This paper shows how NGOs craft framing discourses, and use extant political opportunities and mobilization resources. Focusing on the cases of the Mission of Migrant Workers (MFMW or Mission) and the Asian Migrant Center (AMC), this paper utilizes the theoretical traditions of resource mobilization, political opportunity structure, and framing processes to enrich the analysis of the dynamics that the NGOs have undertaken in the pursuit of foreign domestic workers' (FDW) rights and welfare. The authors present the interactive relationship of factors and frameworks in order to explain the ways in which NGOs, who deal with migrant labor issues, simultaneously frame issues and advocacies in reference to prevailing social conditions and political structures within contextually specific parameters of the host and home societies (i.e. Hong Kong and the Philippines, respectively). By showing the discursive shifts and dynamics of how NGOs frame FDW rights and welfare, this paper underlines the complexity of framing issues across countries as well as the imperatives of identifying structures and opportunities that will allow issues to be presented as relevant to different audiences and in different contexts.